Trends of Values Education Research in Turkey: A Content Analysis of Published Articles - Yazar, Taha; Tutal, Özgür (Dinamika Ilmu, 2020)
In recent years there has been a large increase in the number of research that deal with values education in Turkey. There are several reviews to determine the trends of these studies. However, these reviews were mostly limited to theses, dissertations and proceedings, and it is necessary to review articles on values education. The data of the research conducted with the qualitative research method was gathered by document analysis. 479 articles were included in the research after duplicates and the articles published in non-refereed journals were removed. Content analysis was used to analyze the obtained data. According to the findings of the research; (a) the highest number of articles were published in 2017, (b) qualitative research methods were the most common research methods, (c) most frequently document analysis was preferred as the data collection tool, and content analysis was preferred as the analysis method, (d) data were collected from pre-service teachers the most and purposeful sampling was the most favored sampling method, (e) the sample size is mostly less than 50, (f) mostly the answer to a single research question was sought, (g) the majority of articles were written by two authors, (h) most articles were written by assistant professors as titles and by teachers of the Ministry of National Education on an institutional basis, (i) the articles mostly used domestic sources (j) the majority of the articles were written in Turkish and had not an English extended summary, (k) the most favored journal was The Journal of Values Education.